2011
DOI: 10.1111/j.1746-1561.2011.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Physical Fitness and Academic Performance Among Schoolchildren*

Abstract: Fitness was strongly and significantly related to academic performance. Cardiovascular fitness showed a dose-response association with academic performance independent of other socio-demographic and fitness variables. The association appears to peak in late middle to early high school. We recommend that policymakers consider physical education (PE) mandates in middle high school, school administrators consider increasing PE time, and PE practitioners emphasize cardiovascular fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
165
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(216 citation statements)
references
References 14 publications
32
165
1
8
Order By: Relevance
“…Nonetheless, and despite the plausibility of neurophysiological arguments, evidence of the relationship between AA and CRF and also between AA and PA remains weak (Hillman et al, 2008) and uncertain (TorrijosNiño et al, 2014). Thus to have more robust results on this topic confounding factors such as socio-economic status (SES) and gender and school grade, among others, need to be studied (Active Living Research, 2015;Van Dusen et al, 2011) and objective measures of PA must be considered (Castelli et al, 2007;Esteban-Cornejo et al, 2014a). Studies examining broad age ranges are rare and few studies have specifically examined this issue in Portuguese samples.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, and despite the plausibility of neurophysiological arguments, evidence of the relationship between AA and CRF and also between AA and PA remains weak (Hillman et al, 2008) and uncertain (TorrijosNiño et al, 2014). Thus to have more robust results on this topic confounding factors such as socio-economic status (SES) and gender and school grade, among others, need to be studied (Active Living Research, 2015;Van Dusen et al, 2011) and objective measures of PA must be considered (Castelli et al, 2007;Esteban-Cornejo et al, 2014a). Studies examining broad age ranges are rare and few studies have specifically examined this issue in Portuguese samples.…”
Section: Introductionmentioning
confidence: 99%
“…Year of study 1st year 545 (47) 177 (51) 368 (45) 0.019 2nd year 341 (29) 106 (31) 235 (29) 3rd year 248 (21) 54 (16) 194 (24) ≥ 4th year 23 (2) 6 (2) 17 (2) Age (years) (14) 50 (14) 107 (13) Much worse 20 (2) 13 (4) 7 (1) had normal BMI (healthy weight), and females were significantly more likely to report normal BMI. The majority of students rated their health as excellent/very good/good; reported being health aware very much/to some extent; and rated their quality of life as very well/quite well, although there were significant gender differences across all these variables.…”
Section: Socio-demographicmentioning
confidence: 99%
“…Very little research on aspects of university students' PA has been undertaken in Finland and the very few studies that undertook such a task frequently used small samples (27). This is despite that PA and physical inactivity are well-known protective and risk factors respectively for many chronic conditions; and, in school settings, movement can promote children's cognitive development (28), triggering the need to evaluate the fitness-academic performance connections (29). Since 2000, a national university student health survey in Finland was carried out only four times (30); and there is a dearth of government or country reports dedicated to the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Additional research has found students with low levels of fitness also exhibit low academic scores on achievement tests [17,18]. In particular, it has been reported that children with low levels of fitness exhibit low scores for reading and/or math [19,20].…”
Section: Introductionmentioning
confidence: 99%